Explanation:
If we are solving for t, we have to remember that we have to isolate the variable (get its on its own). Since -1 is with t on the same side of the equation right now, we have to move the -1 to the other side of the equation. To do so, we add it's opposite to the right side (+1). Then, the -1 cancels out so we are left with an isolated t.
-6 = t - 1 (+1)
-6 = t
But we are not done yet! Whatever we do on one side, we have to do on the other side. Since we added 1 to the right, we have to add 1 on the left, too. So we add 1 to -6.
(+1) -6 = t
-6 + 1 = -5
-5 = t
Our final answer: t = - 5 (it can also be written as - 5 = t, but most people prefer the variable going first)